A new targeting agent for the selective drug delivery of nanocarriers for treating neuroblastoma1. Issue 24 (28th June 2015) - Villaverde, Gonzalo; Baeza, Alejandro; Melen, Gustavo J.; Alfranca, Arantzazu; Ramirez, Manuel; Vallet-Regí, Maria
<x xml:space="preserve">Abstract</x> Novel MIBG analogues as targeting agents for neuroblastoma nanomedicines.